hUC-MSCs Therapy with EVs Booster Improves Recovery in Stage 2 Chronic Kidney Disease with Hypercholesterolemia : a case report - Jutadi; Ayu, Dian Respati; Cahyani, Dini; Arda, Adzani Gaisani; Anggoro, Naufal Sebastian (International Journal of Cell and Biomedical Science, 2024)
Hypercholesterolemia is a common metabolic comorbidity that accelerates the progression of chronic kidney disease (CKD). Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) and their secretome, which consist of extracellular vecicles (EVs) and soluble bioactive molecules, have shown potential in modulating inflammation and metabolism. This case report describes significant improvement in serum lipid profile following hUC-MSC and secretome therapy in a patient with stage 2 CKD and hypercholesterolemia. A male patient with CKD stage 2 received two intravenous cycles of hUC-MSC and secretome therapy administered seven months apart. Serial evaluations demonstrated a progressive decline in total cholesterol from 294 mg/dL at baseline to 286 mg/dL after the first treatment and 225 mg/dL after the second. LDL cholesterol decreased from 188 mg/dL to 140 mg/dL, with a mild rebound to 175 mg/dL. HDL cholesterol, initially elevated at 214 mg/dL, showed a modest increase to 220 mg/dL after the first treatment, followed by normalization to 175 mg/dL. Triglyceride levels remained within the normal range (44–51 mg/dL) throughout the observation period. The marked improvement in lipid parameters suggests that hUC-MSC and secretome therapy may exert systemic metabolic regulation via anti-inflammatory, antioxidative, and hepatoprotective mechanisms. hUC-MSC and secretome administration demonstrated potential benefits in lipid homeostasis in a patient with CKD and hypercholesterolemia. These findings support the role of MSC-derived secretome as a promising adjunctive therapeutic approach. Larger controlled trials are warranted to confirm these outcomes and elucidate underlying mechanisms.